Valuation and Development Strategy of Mawar Basecamp in Ungaran Mountain Through Individual Travel Cost Approach - Muhammad Izzuddin Furqony; Fafurida Fafurida (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
Mawar basecamp in Ungaran mountain is one of the potential tourist destinations in Semarang regency. This study aims to identify the variables affect the demand of visits. Secondly, to calculate the economic valuations through the travel cost approach and determine the strategies that can be applied to the development of Mawar Basecamp. This study uses multiple linear regression analysis, economic valuation analysis and SWOT analysis. The result shows that access variables, travel motivation and travel cost have significant effect, while income variable has no significant effect to the demand of Mawar Basecamp visit. The result of economic valuation analysis based on travel cost of visitors shows that the total economic valuation is Rp 8,212,546,988,73 per year. Strategy analysis using SWOT shows that the strategies that can be applied are improving facilities and services, preserving and preserving nature, promotion and cooperation with private and government parties.